Tantangan KPPU Dalam Penegakan Hukum Persaingan Usaha di Era Ekomoni Digital: KPPU - Soesanti, Desy; Widiyanti, Ikarini Dani; Sari, Nuzulia Kumala (Pusat Kajian Hukum Perbankan Fakultas Hukum Universitas Jember, 2024)
The development of technology affects the work system in all fields, including in the field of Business. Technological developments in the business sector are characterized by the emergence of new companies that utilize the internet, these new companies are in the form of Start Up. Business using the internet is more profitable for businesses and consumers so that it makes people flock to open businesses. With the increasing number of business actors, business competition is getting tighter and the potential for business competition violations is also increasing. This is a challenge for the Business Competition Supervisory Commission as an institution that oversees business competition. therefore, this research will discuss the role of the KPPU in enforcing business competition law. this research aims to increase understanding for business actors regarding the legal certainty of business competition in the digital economy era. The research was conducted using normative juridical research methods that are qualitative in nature. In this research, the discussion chapter is a description of the research results. From this research, a new regulation was found regarding violations of fair business competition in business through the internet/digital. As well as known about the actual functions, powers and duties of KPPU.